The Influence of the Number of Employed Population, Gross Regional Domestic Product, and Investment on Regional Original Income in Regencies/Cities of Central Java Province - Ma’ruf Affandi; Agus Budi Santosa (Universitas KH. Abdul Chalim Mojokerto, 2026)
Regional original income is one of the benchmarks in measuring the independence of a region. The achievement of regional original income can be influenced by external factors. This study aims to examine the influence of external factors, namely the number of working population, gross regional domestic product (GDP), and investment, on regional original income with the research object in the Regency/City of Central Java Province during 2018-2024. Data sourced from the Central Statistics Agency (BPS) and the Directorate General of Fiscal Balance, Ministry of Finance. The analytical method used is panel data regression with the fixed effect method. This study concluded that the number of the working population and investment have a significant positive effect on regional original income. Meanwhile, gross regional domestic product does not have a significant effect on regional original income. Simultaneously, the number of employed population, gross regional domestic product, and investment have a significant positive effect on regional original income.